THE INFLUENCE OF COLLABORATIVE LEARNING ON ELEMENTARY SCHOOL STUDENT’S CREATIVE THINKING ABILITY - Mitha, Miftahul Jannah; Miftakhuddin, Miftakhuddin (Kopertis Region IV Jabar and Banten, 2025)
Many studies have explored the effect of collaborative learning on critical thinking skills, social attitudes, and academic achievement; however, few have examined its impact on creative thinking skills. This study aims to identify and analyze the effect of collaborative learning models on the creative thinking skills of fifth-grade students in science learning. This experimental research employed a pretest-posttest control group design. Data were collected from samples in the control and experimental groups (15 students each), using LKS sheets and pretest-posttest instruments that were previously validated for quality (validity and reliability). Statistical analysis through a paired-sample t-test revealed an N-Gain score with a significance (Sig. 2-tailed) value of 0.000 (< 0.05), indicating that Ha was accepted. These results demonstrate that the application of collaborative learning models significantly enhances the creative thinking skills of fifth-grade students. The findings contribute to the ongoing discourse on instructional strategies and support the application of collaborative learning models to foster creative thinking skills in classroom practice.